Effect of low-dose dexmedetomidine on sleep quality in postoperative patients with mechanical ventilation in the intensive care unit: A pilot randomized trial - Sun, Yue-Ming; Zhu, Sai-Nan; Zhang, Cheng; Li, Shuang-Ling; Wang, Dong-Xin (Frontiers in Medicine, 2022)
Background Sleep disturbances are prevalent in patients requiring invasive mechanical ventilation in the intensive care unit (ICU) and are associated with worse outcomes. Sedative dose dexmedetomidine may improve sleep quality in this patient population but is associated with adverse events. Herein, we tested the effect of low-dose dexmedetomidine infusion on night-time sleep quality in postoperative ICU patients with invasive ventilation. Methods In this pilot randomized trial, 80 adult patients who were admitted to ICU after noncardiac surgery and required invasive mechanical ventilation were randomized to receive either low-dose dexmedetomidine (0.1 to 0.2 g/kg/h, n=40) or placebo (n=40) for up to 72 h. The primary endpoint was overall subjective sleep quality measured with the Richards-Campbell Sleep Questionnaire (score ranges from 0 to 100 with higher score indicating better quality) in the night of surgery. Secondary outcomes included sleep structure parameters monitored with polysomnography from 9:00 PM on the day of surgery to the next 6:00 AM. Results All 80 patients were included in the intention-to-treat analysis. The overall subjective sleep quality was median 52 (interquartile 20, 66) with placebo versus 61 (27, 79) with dexmedetomidine, the difference was not statistically significant (median difference 8; 95% CI: -2, 22; P=0.120). Among 68 patients included in sleep structure analysis, those in the dexmedetomidine group tended to have longer total sleep time (median difference 54 min [95% CI: -4, 120]; P=0.061), higher sleep efficiency (median difference 10.0% [95% CI: -0.8%, 22.3%]; P=0.060), lower percentage of stage N1 sleep (median difference -3.9% [95% CI: -11.8%, 0.5%]; P=0.090), higher percentage of stage N3 sleep (median difference 0.0% [95% CI: 0.0%, 0.4%]; P=0.057), and lower arousal index (median difference -0.9 [95% CI -2.2, 0.1]; P=0.091), but not statistically significant. There were no differences between the two groups regarding the incidence of adverse events. Conclusions Among patients admitted to the ICU after surgery with intubation and mechanical ventilation, low-dose dexmedetomidine infusion did not significantly improve sleep quality pattern although there were trends of improvement. Our findings support the conduct of a large randomized trial to investigate the effect of low-dose dexmedetomidine in this patient population.